The impact of different adverse childhood experiences on the dimensions of emotional dysregulation in adults with major depression - Paula Dagnino; Cecilia Cordeu; Eduardo Franco-Chalco; Sergio Gloger; Martín Duisallant; Joaquín Mizon; Loreto Romero (Frontiers in Psychology)
IntroductionAdverse childhood experiences adversely affect the development of emotional regulation, yet their differential impact on discrete dysregulation dimensions in major depressive disorder remains underexamined. This study examines the relationship between adverse childhood experiences and emotional dysregulation, as well as its five dimensions.MethodsA total of 120 out-patients meeting the BDI-II cutoff for MDD completed the Childhood Trauma Questionnaire-SF (CTQ-SF) and the Difficulties in Emotion Regulation Scale (DERS). We first tested sex differences on DERS subscales (none emerged), then ran a multivariate multiple regression using Pillai’s trace to assess the joint effects of the five CTQ-SF dimensions on the five DERS dimensions. Six follow-up linear regressions predicted each DERS subscale and the total DERS score from the CTQ-SF dimensions.ResultsPhysical abuse was the only CTQ dimension with a significant multivariate effect. In univariate models, emotional abuse predicted higher overall dysregulation and increased emotional dyscontrol, everyday interference, and emotional inattention, whereas greater physical abuse was associated with reduced everyday interference.DiscussionEmotional abuse appears to be the principal driver of both global and facet-specific emotion-regulation difficulties in adults with MDD, suggesting that interventions emphasizing impulse control, emotion awareness, and reduction of functional interference may be particularly beneficial for this subgroup.LimitationsThe cross-sectional, selfreport design precludes causal inferences and may be subject to recall bias; future work should employ longitudinal, multimethod approaches to elucidate mechanisms and resilience factors.